Роль кoнтaктoycтанавливающей функции речи в опpеделении формы классического стихотворения - Драздаускене, Мария-Людвика (Kalbotyra, 1990)
The present article is the first publication of research into the significance of the phatic use of language in the English poetry of the 18th century. It reviews results of the investigation included as Chapter 3 in Part 3 of the doctoral thesis of the author or this article, concluded in 1983. The findings are that the phatic use of English, explicitly realized through various forms of address, is extremely frequent in the English poetry of the given period and, in case of the address related to the subject-matter of the verse, determines its linguistic style. The phatic use of English, implicitly realized through the imperative, the declarative sentence and related formulas at the beginning and the end of the verse, like address, performs a double function in the English poetry of the 18th century: the aesthetico-stylistic and the contact establishing. All other openings and closures in the English poetry of this period are rather aesthetico-stylistic than phatic. Their contact establishing effect on the reader is achieved by means of the “emotional blow” produced by them. Hence general communicative and aesthetico-stylistic effectiveness of classical English poetry. An idea of prospective research of this kind within the general theory of uses of language (and the phatic use of English, in particular) is given in conclusion.